Sustainable futures over the next decade are rooted in soil science - Evans, Daniel L.; Janes-Bassett, Victoria; Borrelli, Pasquale; Chenu, Claire; Ferreira, Carla S. S.; Griffiths, Robert I.; Kalantari, Zahra; Keesstra, Saskia; Lal, Rattan; Panagos, Panos; Robinson, David A.; Seifollahi-Aghmiuni, Samaneh; et al. (Wiley, 2021)
The importance of soils to society has gained increasing recognition over the past decade, with the potential to contribute to most of the United Nations’ Sustainable Development Goals (SDGs). With unprecedented and growing demands for food, water and energy, there is an urgent need for a global effort to address the challenges of climate change and land degradation, whilst protecting soil as a natural resource. In this paper, we identify the contribution of soil science over the past decade to addressing gaps in our knowledge regarding major environmental challenges: climate change, food security, water security, urban development, and ecosystem functioning and biodiversity. Continuing to address knowledge gaps in soil science is essential for the achievement of the SDGs. However, with limited time and budget, it is also pertinent to identify effective methods of working that ensure the research carried out leads to real-world impact. Here, we suggest three strategies for the next decade of soil science, comprising a greater implementation of research into policy, interdisciplinary partnerships to evaluate function trade-offs and synergies between soils and other environmental domains, and integrating monitoring and modelling methods to ensure soil-based policies can withstand the uncertainties of the future.
Keywords: Sustainable Development Goals; Climate change; Food security; Water security; Urban development; Ecosystems; Biodiversity